(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Ifosfamide is an alkylating agent, frequently used in the treatment of sarcoma. Major side effects of ifosfamide are classified as nephropathy, neuropathy, and hematologic complications. The aim of present study was to determine the frequency and severity of ifosfamide nephropathy in patients with various types of sarcoma. Materials and Methods. Ninety patients (52 males and 38 females) who had received ifosfamide chemotherapy for sarcoma were included in this study. Data on physical examination, laboratory studies, and estimation of glomerular filtration rate were collected. The median duration of follow-up was 6 to 12 months. Records of documented nephropathy were identified in these patients. Results. The age range of patients on ifosfamide was 5 to 59 years. Thirty-four of the patients were children and 56 were adults. The most common renal side effects were proteinuria (15.5%), glycosuria (7.8%), elevation of serum creatinine (2.2%), hematuria (14.4%), and combination of proteinuria and glycosuria (5.5%). None of the patients had gross hematuria, but microscopic hematuria was present in 14.4%. Conclusions. Ifosfamide nephropathy was seen with different degrees of severity in patients with sarcoma. Monitoring of the side effects of ifosfamide should be revised in different populations.